Estudo computacional da condutividade térmica de nanofios de Si - Lorenset, Guilherme Aluizio Steffens (2014)
In this work the thermal conductivity κ of Si nanowires using molecular dynamics simulations is calculated using the Müller-Plathe method. We show that at 500 K, κ for crystaline Si is 121; 557 W/mK, while for nanowires, with 54; 300 nm of length and square section of 4; 717 nm2, value is 3; 419 - 0; 053 W/mK, demonstrating a reduction of two orders of magnitude relative to crystal Si. Variations in length, diameter and temperature are studied and the results follow the macroscopic characteristics, where κ in nanowires is directly proportional to length and diameter and inversely proportional to temperature. However, an increase of 45% for κ in nanowires with growth direction [110] in relation to the directions [100] and [111] is found. The values of κ for nanowires with length 54; 300 nm and the growth direction [110] is about 4; 941 - 0; 107 W/mK, while in the direction [111] is about 3; 406 - 0; 087 W/mK. A brief study of the geometric shape of the cross section of the nanowires is performed, with a reduction of 20% is calculated on nanowires with cylindrical and rhombic section nanowires compared to same diameter and square section. The values found for κ are 2; 663-0; 043 W/mK and 2; 811-0; 038 W/mK for cylindrical nanowires and rhombohedral, respectively.